SISTEM INFORMASI PENGELOLAAN KEUANGAN SEKOLAH BERBASIS WEB PADA SMK WIWOROTOMO - Muh Sofi'i; Wika Purbasari; Joko Purnomo (LPPM STMIK Widya Utama, 2018)
The purpose of this research is to create a WEB-Based School Financial Management Information System at Wiworotomo Vocational School. This research was carried out because of the gap between expectations and reality in financial management in SMK Wiworotomo and was also strengthened by previous researchers regarding the importance of using Information Technology to improve the performance of school financial management. The modules produced in this system can all run well and can provide information as expected, this is necessary from the black box test on the application module which are all valid, successfully meeting the researchers' expectations. The implementation of this system will improve the performance of financial and service performance and school financial management, so that management can at any time know in real time the transactions that occur, no need to wait for manual reports from the financial department, so also students can independently know the obligations and performance of each financial activities.